The Relationship Between Basic Sanitation and Awareness in the Velho Dam (Global Journal of Human-Social Science, 2024)
This article aims to describe the damage caused to the population and the environment with the dumping of untreated effluents in the Old Dam located in the municipality of Salgueiro -PE, considering the possible diseases that can cause for the residents and the damage to aquatic animal life. Within this context, this work proposes to present the methodology of basic research and field research in the study area of the dam, emphasizing the inhabitants' perceptions about the characteristics of the studied area due to the lack of sanitation.
Keywords: weir; sanitation; search; illness; Salgueiro-PE